2013
DOI: 10.1371/journal.pone.0057915
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adiposity, Dysregulated Glucose Metabolism and Systemic Inflammation in Galectin-3 KO Mice

Abstract: Obesity and type 2 diabetes are associated with increased production of Galectin-3 (Gal-3), a protein that modulates inflammation and clearance of glucose adducts. We used Lean and Diet-induced Obese (DIO) WT and Gal-3 KO mice to investigate the role of Gal-3 in modulation of adiposity, glucose metabolism and inflammation. Deficiency of Gal-3 lead to age-dependent development of excess adiposity and systemic inflammation, as indicated by elevated production of acute-phase proteins, number of circulating pro-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 41 publications
11
87
2
Order By: Relevance
“…Data on galectin-3 inhibition are not univocal, however, and galectin-3 deletion exacerbates systemic inflammation, hyperglycemia, and liver and kidney injury in diet-induced obese rodents (88). It has been suggested that inhibition of AGE uptake by the liver, which clears .90% of these end products from the circulation, promotes the systemic accumulation of AGEs and receptor for AGE (RAGE)-mediated uptake by other tissues, thereby aggravating extrahepatic toxicity of these molecules.…”
Section: Targeting Molecular Effectors Of Inflammation and Fibrosismentioning
confidence: 99%
“…Data on galectin-3 inhibition are not univocal, however, and galectin-3 deletion exacerbates systemic inflammation, hyperglycemia, and liver and kidney injury in diet-induced obese rodents (88). It has been suggested that inhibition of AGE uptake by the liver, which clears .90% of these end products from the circulation, promotes the systemic accumulation of AGEs and receptor for AGE (RAGE)-mediated uptake by other tissues, thereby aggravating extrahepatic toxicity of these molecules.…”
Section: Targeting Molecular Effectors Of Inflammation and Fibrosismentioning
confidence: 99%
“…Two independent research laboratories investigated the role of galectin-3 in the modulation of metabolic disorders induced by an obesogenic HFD containing 60% calories from saturated fat [92,93]. Both studies demonstrated a protective role of galectin-3 toward obesity and type 2 diabetes, via modulation of the responsiveness of innate and adaptive immunity to overnutrition [92,93].…”
Section: Galectin-3 As a Disease Mediator: Animal Studiesmentioning
confidence: 99%
“…Additionally, Pejnovic et al (18) reported significantly increased IFN-γ-producing Type 1 T/NKT cells and proinflammatory M1 macrophages and reduced T regulatory cells and alternatively activated M2 macrophages in the VAT of LGALS3 -/-mice fed a HFD compared with diet-matched WT animals. Pang et al (27) reported that Gal-3-deficient mice fed a HFD for 12 weeks develop increased adiposity and systemic inflammation. In addition, the same authors showed that despite the increased adiposity in Gal-3-deficient mice, there was no significant difference in the size of the adipocytes (27).…”
Section: Discussionmentioning
confidence: 99%
“…Pang et al (27) reported that Gal-3-deficient mice fed a HFD for 12 weeks develop increased adiposity and systemic inflammation. In addition, the same authors showed that despite the increased adiposity in Gal-3-deficient mice, there was no significant difference in the size of the adipocytes (27). In this study, we demonstrated that LGALS3-/-mice fed a HFD for 6 months developed visceral adiposity, hyperglycaemia and IR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation